Giardia lamblia: missing evidence for a canonical thioredoxin system. (30th October 2017) - Leitsch, David; Rout, Samuel; Lundström-Stadelmann, Britta; Balmer, Vreni; Hehl, Adrian; Müller, Norbert
Abstract: The microaerophilic protozoan parasite Giardia lamblia occurs globally and causes dysentery in humans and animals. Since it is very sensitive to oxygen and reactive oxygen species, G . lamblia disposes over several enzymatic pathways to counter oxidative stress. One of the enzymes involved is thioredoxin reductase (TrxR), a central redox regulator that indirectly reduces peroxiredoxins via thioredoxin, an electron shuttle protein. Interestingly, the components of the TrxR-mediated redox system, including functional thioredoxins, have so far not been described despite their surmised importance for parasite survival. We aimed at filling this gap and attempted to identify functional thioredoxins and other interaction partners of TrxR in G . lamblia . To this end, we conducted database searches and expressed three recombinant candidate thioredoxins in Escherichia coli for ensuing enzyme assays. Further, co-immunoprecipitation experiments were conducted in order to identify further components of the thioredoxin redox network. Finally, the cellular localization of TrxR and peroxiredoxin 1 was determined by immunofluorescence microscopy. Surprisingly, our endeavours did not result in the identification of a functional thioredoxin or other credible interaction partners of TrxR. We, therefore, conclude that there is currently no evidence for a canonical thioredoxin redox network in G . lamblia .